Establishing the dependence of fermentation process of milk clots with mesophilic lactic acid streptococci on the genotype of cows in terms of the kappa-casein gene - Ladyka, Volodymyr; Skliarenko, Yury; Bolgova, Nataliia; Vechorka, Viktoriia; Tereshchenko, Serhiy; Pysariev, Vitalii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of research is patterns in a technological process related to the fermentation of milk clots from dairy raw materials obtained from cows with different genotypes by the kappa-casein gene. The task still unresolved is the need to adjust the technological process in the manufacture of fermented milk products from dairy raw materials obtained from cows with different genotypes by this gene. This is associated with the interest of animal owners to create herds of cows with the BB genotype in order to improve milk suitability for cheese making. Changes in physical-chemical, microbiological, and organoleptic parameters in the process of targeted use of mesophilic lactic acid bacteria of biotechnological processing and during storage have been studied. Based on the results of the study of fermented clots, their physical-chemical and microbiological parameters, the absence of dependence of the fermentation process of milk clots by mesophilic lactic acid streptococci on the cow genotype according to the kappa-casein gene has been found. The study has resulted in confirming the hypothesis that genetic variants of the kappa-casein (CSN3) gene in cows (AA, AB, BB) affect the physical-chemical characteristics of milk, the dynamics of fermentation, and the properties of milk clots formed under the action of mesophilic lactic acid streptococci, and therefore the quality of finished fermented milk products. The use of milk from the cow genotype based on the kappa-casein gene is possible using classical technology and does not require adjustment of technological conditions. The results of the work could be used in the milk processing industry in the development of technology for fermented milk products from raw milk of cows with different genotypes based on the kappa-casein gene